2017
DOI: 10.1080/1028415x.2017.1380892
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic and neuroinflammatory changes induced by consuming a cafeteria diet are age-dependent

Abstract: The 3- and 18-month-old rats responded differently to a cafeteria diet. Insulin and leptin levels are elevated in young animals fed a cafeteria diet, whereas aged animals are prone to neuroinflammation (indicated by an increase in interleukin-1β levels). A combination of hypercaloric diet and senescence have detrimental effects on the inflammatory response in the brain, which may predispose to neurological diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 68 publications
2
14
0
1
Order By: Relevance
“…www.nature.com/scientificreports/ Mice that consumed HFHS as adults showed increased microgliosis in the PrL PFC and all hippocampal subregions measured by IBA-1 fluorescence compared to the adolescent cohort, which was also associated with increased adiposity. Given that microglia respond to cytokines, this observation suggests that there may be some resistance to HFHS-induced neuroinflammation in younger animals, which has been previously observed in rats 44 . However, when we examined morphological changes in microglia-from resting (ramified) to active (hypertrophied) states-we found a significant reduction in ramified microglia and related increases in hypertrophied microglia within the PFC of mice exposed to the HFHS-diet during adolescence, but not as adults, which was positively correlated with adiposity.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…www.nature.com/scientificreports/ Mice that consumed HFHS as adults showed increased microgliosis in the PrL PFC and all hippocampal subregions measured by IBA-1 fluorescence compared to the adolescent cohort, which was also associated with increased adiposity. Given that microglia respond to cytokines, this observation suggests that there may be some resistance to HFHS-induced neuroinflammation in younger animals, which has been previously observed in rats 44 . However, when we examined morphological changes in microglia-from resting (ramified) to active (hypertrophied) states-we found a significant reduction in ramified microglia and related increases in hypertrophied microglia within the PFC of mice exposed to the HFHS-diet during adolescence, but not as adults, which was positively correlated with adiposity.…”
Section: Discussionsupporting
confidence: 73%
“…Obesity is also associated with chronic inflammation due to the systemic release of inflammatory cytokines by adipocytes 42 , which then enter the brain via the blood brain barrier causing neuroinflammation 43 . The effects of obesogenic diets on neuroinflammation might occur in an age-dependent manner, with younger rats being more resistant to obesity-induced neuroinflammation, indicated by an increase in cortical interleukin-1β levels in 18-month-old, but not 3-month-old rats 44 . What has not yet been examined, however, is the role of microglia in HFHS-induced pathology across age groups.…”
mentioning
confidence: 99%
“…It has also been shown that this response is age-dependent. Though, normally aged individuals are more prone to diet-induced neuroinflammation than young individuals 71 . Here, younger mice show a more pronounced inflammatory response to SRD.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, some studies have not observed significant differences in inflammatory biomarkers following adolescent HFD access (Kaczmarczyk et al, 2013; Wang et al, 2015). Recent evidence suggests that aged animals may be more susceptible to neuroinflammation following access to a cafeteria diet (Teixeira et al, 2019), suggesting an additional developmental period of vulnerability to high fat, high sugar diets.…”
Section: Discussionmentioning
confidence: 99%